2019
DOI: 10.1093/nar/gkz1109
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination repair intermediates promote efficient de novo telomere addition at DNA double-strand breaks

Abstract: The healing of broken chromosomes by de novo telomere addition, while a normal developmental process in some organisms, has the potential to cause extensive loss of heterozygosity, genetic disease, or cell death. However, it is unclear how de novo telomere addition (dnTA) is regulated at DNA double-strand breaks (DSBs). Here, using a non-essential minichromosome in fission yeast, we identify roles for the HR factors Rqh1 helicase, in concert with Rad55, in suppressing dnTA at or near a DSB. We find the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
3
11
0
Order By: Relevance
“…Extensive LOH was significantly reduced in rqh1Δ exo1Δ Ch 16 -Tel-DSB cells, consistent with Ch I formation requiring extensive processing (11,12) ( Fig. 1D), with LOH resulting instead from de novo telomere addition (dnTA) (13).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Extensive LOH was significantly reduced in rqh1Δ exo1Δ Ch 16 -Tel-DSB cells, consistent with Ch I formation requiring extensive processing (11,12) ( Fig. 1D), with LOH resulting instead from de novo telomere addition (dnTA) (13).…”
supporting
confidence: 62%
“…S4, H and I).LOH9 exhibited a duplication of a larger portion the centromeric region, explaining the increased minichromosome size compared to LOH1(fig. S4I).In contrast, LOH5, was found to have retained some of the right arm, consistent with de novo telomere addition(13,21) (fig. S4J).…”
supporting
confidence: 52%
“…This sequence can then be used as a template for largely accurate repair. Meanwhile, extended DNA end resection contributes to nonligatable DNA breaks and hampers end joining; consequently, DNA end resection is dominant [186][187][188] . Hence, HR is initiated only when a repair template exists, which can limit the potential for illegitimate recombination.…”
Section: Dna Dsb Repair Pathwaysmentioning
confidence: 99%
“…It has been shown that truncation ends are healed by de novo telomere addition (Dave et al, 2020;Matsumoto et al, 1987;Pennaneach et al, 2006). To determine the chromosomal sites to which telomere sequences have been added, we amplified the breakpoints using a pair of ChL C and telomere primers: M13R-C19 or M13R-T1 (Irie et al, 2019) and chromosomal truncations recovered from agarose gels.…”
Section: Fission Yeast Rad8 Facilitates Isochromosome Formation But Nmentioning
confidence: 99%